(untitled) (Journal of the College of Education for Women, 2019)
This Study aimed To know The relation between Types of blood and health problems which human Suffered from , and the effect of food intake on health.Samples of study contained 269 person aged between 30 – 70 years which choiced randomly for sex , we are take all in formation about samples of study by form paper contian sex , age, type of blood , weight (kg) , height (cm) , smoking or.not , sporting or not, problems in digestive tract , sensitivity for foods , heart problems , ratio of cholesterol in blood , Sinusitis , Asthma , diabetic meliuts , arritable bowel syndrome , diaherra , problems in kidney and urination , hypertension , anemia , alternation in liver function , arthritis with form record in daily food intake and its adequacy to dam the recommended dietary allowances from food groups .Results reffer that we found no effect of sex on health problems as types of blood and we will found relation and effect of type of blood on health problems according to the kind of food intake .Also we will found relation with these types of blood according to some health problems as well as A , AB , This relation effect in weight disturbance , problems in digestive tract , high ratio of cholesterol , problems in kidney and urination .O , AB , This relation effect in weight disturbance , problems in digestive tract , high ratio of cholesterol and urination .A , B and A,0 These two relation effect in breath problems , and arthritis and defect in food groups .We also found relation between type of blood A with others type of blood which effect on food sensitivity to some foods .